2017
DOI: 10.1186/s12879-017-2722-0
|View full text |Cite
|
Sign up to set email alerts
|

Future complications of chronic hepatitis C in a low-risk area: projections from the hepatitis c study in Northern Norway

Abstract: BackgroundHepatitis C (HCV) infection causes an asymptomatic chronic hepatitis in most affected individuals, which often remains undetected until cirrhosis and cirrhosis-related complications occur. Screening of high-risk subjects in Northern Norway has revealed a relatively low prevalence in the general population (0.24%). Despite this, late complications of HCV infection are increasing. Our object was to estimate the future prevalence and complications of chronic HCV infection in the period 2013–2050 in a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 60 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Primary care practitioners can play an important role in targeted screening, especially in former PWID, whereas screening of current PWID is more appropriate in settings like outpatient clinics, opioid substitution programs, jails, and psychiatric clinics [17,[42][43][44][45][46]. In a screening and medical follow-up programme in Northern Norway, primary care practitioners were encouraged to screen patients with former or present risk factors for HCV infection, which led to an increase in the number of newly diagnosed HCV infections in the subsequent years [47]. Technical bottlenecks in HCV testing can lead to missed opportunities in the HCV cascade of care, e.g., when a high proportion of anti-HCV positive individuals are not followed up with a confirmatory test for HCV RNA [48].…”
Section: Screening Strategies In a Low-prevalence Area: Whom And How mentioning
confidence: 99%
“…Primary care practitioners can play an important role in targeted screening, especially in former PWID, whereas screening of current PWID is more appropriate in settings like outpatient clinics, opioid substitution programs, jails, and psychiatric clinics [17,[42][43][44][45][46]. In a screening and medical follow-up programme in Northern Norway, primary care practitioners were encouraged to screen patients with former or present risk factors for HCV infection, which led to an increase in the number of newly diagnosed HCV infections in the subsequent years [47]. Technical bottlenecks in HCV testing can lead to missed opportunities in the HCV cascade of care, e.g., when a high proportion of anti-HCV positive individuals are not followed up with a confirmatory test for HCV RNA [48].…”
Section: Screening Strategies In a Low-prevalence Area: Whom And How mentioning
confidence: 99%
“…The study of Kileng et al, 28 showed that the rate of fibrosis appeared to be slow in the first 20-25 years of infection, while it increased in subsequent years, especially in specific genotype, 29 therefore suggesting a non-linear age-related progression of the disease. 27,28 In addition, several studies found that age at infection is highly associated with fibrosis progression and, then with HCV-related complications. 30,31 Indeed, the higher rate of progression in liver damage was found in patients with older age at infection than in patients infected at younger age.…”
Section: Discussionmentioning
confidence: 99%
“…The disease burden and serious complications due to HCV infection are projected to increase over the next few decades [ 22 , 23 ]. It is expected that liver disease complications will increase by three- to four-fold under the current treatment scenario, even in countries with a very low viremic prevalence (0.2–0.5% among adults) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although effective IFN-free DAA treatment can improve the therapeutic response (>90% with SVR), the cumulative death due to CHC depends on the treatment coverage and allocation strategies [ 16 ]. In Norway, increasing the coverage of DAA treatment to 50% is speculated to be able to reduce the incidence of cirrhosis by half [ 22 ], while, in Iran, doubling or stepwise increase in the current coverage is expected to reduce the number of deaths by >60% by 2030 [ 23 ]. Similar projections have been calculated for Thailand, in that the current cumulative HCV-related death will diminish (25.5% reduction), and CHC prevalent will decline to nearly zero under expanded treatment strategy (DAA based-therapy) by increasing in fivefold increments of the current coverage (3,000 treatments in 2015) over the next 20 years [ 16 ].…”
Section: Discussionmentioning
confidence: 99%